Suicide Ideation and Depression among High-School Students in Mexico - de la Roca Chiapas, José María; Tapia Ibarra, Iliana Pamela; Huerta Lepez, José Eduardo; Paramo Castillo, Daniel; Ramos Frausto, Víctor; Pérez Sánchez, Lucía (Pensando Psicología, 2020)
Purpose: To analyse the levels of depression and its influence on the presence of suicide ideation among high-school students. Methods: cross-sectional, observational, and comparative study. The sample included 447 students who answered the following: the Beck Depression Inventory, the Beck Scale for Suicide Ideation, the Hamilton Scale for depression and a risk factor questionnaire elaborated ex professor. Statistical analysis included a description of variables, Pearson’s correlation coefficient, and multiple regression. Results: Sixty-six students (14.8%) presented with suicide risk and 29 had made a suicide attempt. Almost 34% of the students presented some level of depression according to the Hamilton Scale. Conclusions: There is a strong correlation between suicidal behaviours and depression. It is important to raise awareness of the early signs of depression as a risk factor that may potentiate the risk of a suicide attempt.